Stem-Loop RNA Hairpins in Giant Viruses: Invading rRNA-Like Repeats and a Template Free RNA - Seligmann, Hervé; Raoult, Didier (Frontiers in Microbiology, 2018)
We examine the hypothesis that de novo template-free RNAs still form spontaneously, as they did at the origins of life, invade modern genomes, contribute new genetic material. Previously, analyses of RNA secondary structures suggested that some RNAs resembling ancestral (t)RNAs formed recently de novo, other parasitic sequences cluster with rRNAs. Here positive control analyses of additional RNA secondary structures confirm ancestral and de novo statuses of RNA grouped according to secondary structure. Viroids with branched stems resemble de novo RNAs, rod-shaped viroids resemble rRNA secondary structures, independently of GC contents. 5' UTR leading regions of West Nile and Dengue flavivirid viruses resemble de novo and rRNA structures, respectively. An RNA homologous with Megavirus, Dengue and West Nile genomes, copperhead snake microsatellites and levant cotton repeats, not templated by Mimivirus' genome, persists throughout Mimivirus' infection. Its secondary structure clusters with candidate de novo RNAs. The saltatory phyletic distribution and secondary structure of Mimivirus' peculiar RNA suggest occasional template-free polymerization of this sequence, rather than noncanonical transcriptions (swinger polymerization, posttranscriptional editing).